AGILE LEADERSHIP DARI PERSPEKTIF MENCIPTAKAN NILAI - James, James; Donal Devi Amdanata (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2023)
Agile leadership is a concept that emphasizes a leader's ability to adapt quickly, make informed decisions, and create value for the organization. In a constantly changing and complex environment, agile leadership becomes a highly important quality. This concept involves sensitivity to change, critical thinking ability, visionary leadership, and the capacity to innovate. In terms of creating value, agile leadership plays a crucial role. Agile leaders are able to identify new opportunities, develop innovative strategies, and deliver significant outcomes for the organization and stakeholders. Agile leaders are capable of building strong teams, developing the skills and potential of team members, and creating a positive and inclusive work environment. In the approach of agile leadership, it is important to create an organizational culture that encourages innovation and development.